THE US’ CONTAINMENT STRATEGY AGAINST CHINA AND ITS IMPACT ON THE US-CHINA RELATIONS AT INTERNATIONAL SYSTEM LEVEL - Anh, Nguyen Ngoc (VNU Journal of Foreign Studies; Vol 35 No 2, 2019)
The article analyzes the US’ containment strategy against China at international system level, including the reason, main actions, and impact of this strategy on the US-China relations. The article supposes the main reason for making the strategy is the US’ desire to preserve her hegemony over the rise of China. The strategy consists of five main moves: economic restraint, technology restraint, restraint of territorial sovereignty ambition, assault on soft power, military deterrence, and prevention of coalition alliances. These moves will make the US-China relationship increasingly tense. However, except for the excess of the limit of restraining territorial sovereignty ambition, especially related to Taiwan, the other moves may make the US-China relations tense, but will not drive these two countries to war.